RNA binding protein serine/arginine splicing factor 1 promotes the proliferation, migration and invasion of hepatocellular carcinoma by interacting with RecQ protein-like 4 mRNA. Issue 1 (1st January 2021) - Ye, Ying; Yu, Feng; Li, Zhao; Xie, Yaping; Yu, Xiaohong
ABSTRACT: Abnormally high expression of RecQ protein-like 4 (RECQL4) has been observed in many cancers, including hepatocellular carcinoma (HCC). We aimed to explore the effects of RECQL4 on HCC progression and the possible mechanisms. RECQL4 expression in HCC tissues and its correlation with the prognosis of HCC patients were analyzed using GEPIA2 and UALCAN databases. After detecting RECQL4 levels in several human HC cell lines, RECQL4 was silenced by siRNA transfection. Cell viability, migration and invasion were tested with CCK-8, wound healing and transwell assays. The levels of epithelial–mesenchymal transition (EMT) proteins were evaluated by western blotting. The ENCORI database was adopted for the analysis of the correlation between RECQL4 and serine/arginine splicing factor 1 (SRSF1) in HCC tissues. RNA immunoprecipitation and actinomycin D addition assay were employed to evaluate the combination of these two genes. SRSF1 was overexpressed to assess the biological function of HCC cells with RECQL4 silencing. Results suggested that RECQL4 was overexpressed in HCC tissues and cell lines, which was related to poor prognosis of HCC patients. RECQL4 loss-of-function repressed the proliferation, migration, invasion and EMT of HCC cells. RECQL4 was positively correlated with SRSF1 in HCC tissues. Moreover, SRSF1 was confirmed as an RNA binding protein of RECQL4. Further experiments found that SRSF1 knockdown reduced the stability of RECQL4 mRNA. Rescue assays indicated that SRSF1 overexpression crippled the braking effects of RECQL4 knockdown on the progression of HCC cells. Collectively, SRSF1 can bind to RECQL4 mRNA and enhance its stability, thereby promoting the progression of HCC.